Making it work ; Fighting fumes ; National treasures [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1994)
Documents unleaded gasoline putting a stop to air pollution, G.S.I.S. 34 million dollars overseas investments and the indigenous artistic culture like Ambahan, Basal and Kudyapi.
Make it work (16 min.) -- Fighting fumes (14 min.) -- National treasures (15 min.)
VHS.
Keywords: Government Service Insurance System; Gasoline -- Philippines; Ambahans (Mangyan verbal contest); Filipino poetry; Investment of public funds -- Philippines